Biowaste Mixtures Affecting the Growth and Elemental Composition of Italian Ryegrass (Lolium multiflorum). Issue 3 (1st May 2016) - Esperschütz, Jürgen; Lense, Obed; Anderson, Craig; Bulman, Simon; Horswell, Jacqui; Dickinson, Nicholas; Robinson, Brett
Abstract : Biosolids (sewage sludge) can be beneficially applied to degraded lands to improve soil quality. Plants grown on biosolids‐amended soils have distinct concentrations of macronutrients and trace elements, which can be beneficial or present a risk to humans and ecosystems. Potentially, biosolids could be blended with other biowastes, such as sawdust, to reduce the risks posed by rebuilding soils using biosolids alone. We sought to determine the effect of mixing biosolids and sawdust on the macronutrient and trace element concentration of ryegrass over a 5‐mo period. Lolium multiflorum was grown in a low fertility soil, typical for marginal farm areas, that was amended with biosolids (1250 kg N ha −1 ), biosolids + sawdust (0.5:1) and urea (200 kg N ha −1 ), as well as a control. Biosolids increased the growth of L. multiflorum from 2.93 to 4.14 t ha −1 . This increase was offset by blending the biosolids with sawdust (3.00 t ha −1 ). Urea application increased growth to 4.93 t ha −1 . The biowaste treatments increased N, P, Cu, Mn, and Zn relative to the control, which may be beneficial for grazing animals. Although biowaste application caused elevated Cd concentrations (0.15–0.24 mg kg −1 ) five‐ to eightfold higher than control and urea treatments, these were below levels that are likely to result in unacceptable concentrations in animal tissues. Mixing biosolids with sawdust reduced Cd uptake while still resulting in increased micronutrient concentrations (P, S, Mn, Zn, Cu) in plants. There were significant changes in the elemental uptake during the experiment, which was attributed to the decomposition of the sawdust. Core Ideas: Biowastes (biosolids + sawdust) were effective in improving a low‐fertility soil. The biowaste mixture improved growth and quality of Lolium multiflorum over 5 months. The biowaste treatments increased N, P, Cu, Mn, and Zn. Mixing biosolids with sawdust reduced Cd uptake. Biowaste induced changes in elemental composition increased over the 5‐month period.